CO2 conversion to syngas through the steam-biogas reforming process. (May 2018) - Roy, Partho Sarothi; Song, Jinwoo; Kim, Kiseok; Park, Chan Seung; Raju, Arun S.K.
Highlights: Equilibrium CH4, CO2 conversion of SBR process increases with decreasing CH4 % in biogas. SBR over Pd-Rh is compared with equilibrium values predicted by Aspen Plus and CH4 conversion rates are comparable. At S/C ratio of 1.50 and 1073 K or above, positive CO2 conversion is obtained. SBR coke formation is significantly reduced over Pd-Rh compared to literature data. SBR integrated with combustion process works with an efficiency of 40% or higher. Abstract: The steam-biogas reforming (SBR) process to convert biogas to a high hydrogen syngas was studied experimentally and using Aspen Plus simulations. An integrated renewable power generation system where the SBR process was coupled with a Solid Oxide Fuel Cell (SOFC) was studied using the Aspen Plus model. The experimental work was conducted over a metal-foam-coated [Pd(7)-Rh(1)]/[CeZrO2 (25)-Al2 O3 (75)] catalyst in a Heat Exchanger Platform (HEP) reactor. SBR simulations were conducted for biogas feeds with CH4 /CO2 ratios of 40/60, 50/50 and 60/40 at S/C ratios of 1.00–2.00 over a temperature range of 873–1123 K. The experimental data show that positive CO2 conversion was attainable only at temperatures higher than 1073 K, although the equilibrium based simulation predicts positive CO2 conversion through most of the operating temperature range. Energy efficiency of the overall system was approximately 40% at temperatures of 948 K and above. Coke formation over the Pd-Rh catalyst was estimated to be 1.05–2.88% of the carbon input to the system. Fresh and used catalysts were characterized by BET adsorption, porosimetry, CO chemisorption and Scanning Electron Microscopy. The results show that the proposed system can provide a viable approach to utilizing distributed renewable methane resources for localized power generation.